Ubiquitin-specific protease 1 overexpression indicates poor prognosis and promotes proliferation, migration, and invasion of gastric cancer cells. (February 2022) - Meng, Debin; Li, Delong
Highlights: The expression of USP1 mRNA in different kinds of human cancers. Prognostic value of USP1 mRNA in human malignancies. Correlation of USP1 mRNA and clinical prognosis in GC. USP1 promoted the proliferation of GC cells in vitro. USP1 promoted the migration and invasion of GC cells in vitro. Abstract: Ubiquitin-specific protease 1 (USP1) has been documented to involved in the occurrence and development of different kinds of malignancies, containing breast cancer, glioma and prostatic cancer. However, the role of USP1 in gastric cancer (GC) is still obscure. In method, gene expression profiling interactive analysis and Kaplan-Meier Plotter databases were applied to analyze the prognostic value of USP1 in human cancers. The expression of USP1 was evaluated by quantitative reverse transcription polymerase chain reaction assay and western blotting. Cell proliferation, migration, and invasion abilities were detected to determin the role of USP1 in the tumorigenesis of GC. As a result, USP1 was upregulated in GC samples relative to its paired normal samples. USP1 was a valuable diagnostic marker for GC, and its overexpression indicated the poor overall survival time of patients with GC. More importantly, USP1 levels were increased in GC cells and its silencing restrained the proliferation, migration, invasion and epithelial-to-mesenchymal transition (EMT) of GC cells. In Conclusion, USP1 was upregulated in GC, and might be a valuable diagnostic and prognostic marker for GC. Moreover, USP1 silencing hindered the proliferation, migration, invasion, and EMT of GC cells, revealing the oncogenic role of USP1 in GC progression.